Strategic pricing for the arts - Rushton, Michael, 1959- (Routledge, Taylor & Francis Group, 2015)
"Pricing is complex, especially in the creative and cultural sector. How should prices differ between ordinary and premium seating? How much of a discount in admission should be offered through membership or season subscription? Does it make sense to charge higher ticket prices but offer relatively low mark-ups on refreshments available inside the venue, or to have lower ticket prices but a high mark-up on refreshments? When does it make sense to partner with organizations (possibly not from the arts) to offer discounts? When should nonprofit or state arts organizations depart from profit-maximizing pricing strategies? Should ticket prices for a single performance remain fixed, or can it be beneficial to raise or lower ticket prices in response to surprisingly high, or low, demand? This accessible text provides a concise, practical, non-technical guide for setting prices. It brings the insights of sophisticated research into the art of pricing to the working arts manager or student, in accessible language, appropriate for students or practitioners with no formal training in economics"--